Transmigrant impacted mandibular canine: a case report - Tila Fortuna; Deyvid da Silva Rebouças; Wilton Costa Neto; Lucas Souza Cerqueira; Lívia Prates Soares Zerbinati; Adriano Freitas de Assis (Brazilian Dental Science)
Transmigration of canines across mandibular midline is a rare and elusive phenomenon described in the dental literature. Etiology of this phenomenon is obscure, but in some cases supernumerary teeth may be one of the causes. Surgical extraction is indicated due to pathologic lesions, infection, trauma to the adjacent teeth, pain, ectopic eruption, and interference with prosthesis. The aim of this case report is to describe the treatment of transmigrant impacted mandibular canine near to the mandibular symphysis and to review the literature about its incidence, prevalence, and treatment options. In the anterior mandible, labial access was performed followed by osteotomy and odontosection, for tooth removal. Canine impaction is more prevalent in the maxilla than in the mandible, but canine transmigration is more frequent in the mandible. Females seem to be more affected than males, and the left side is more prevalent than the right. Although the literature is controversial about treatment protocol for transmigrant teeth, several authors indicate its extraction to prevent lesions that are associated with impacted teeth, especially when orthodontic traction is contraindicated due to the position of those teeth.